Soviet observer / W. Averell Harriman Institute for Advanced Study of the Soviet Union, Columbia University - Averell Harriman Institute for Advanced Study of the Soviet Union. (The Institute, 1990)
Published by students at The W. Averell Harriman Institute for Advanced Study of the Soviet Union, Columbia University.Current frequency: 24/year.